The development of a community-based, problem-based learning curriculum in the undergraduate degree in nursing with special emphasis on the child-bearing women in women's health - Mc Inerney, Patricia Anne-Marie (My University, 2014)
A conceptual framework was developed based on Fawcett’s conceptual framework and Stufflebeam’s Decision Making Model. The merging of the concepts of the framework and the model gave rise to the concepts of the research model, viz. environment, registered midwife, curriculum and outcome. These concepts were researched. Donabedian’s Quality Assurance Model and Parlett and Hamilton’s Illuminative Evaluation guided the research methodology. The methodology adopts a triangulated approach, making use of both quantitative and qualitative data collection procedures. In order to study the concept “environment” 250 women were interviewed post-natally in order to determine their perceptions and expectations of care during pregnancy, labour and the puerperium. The findings show that women are not empowered in terms of their expectations of care. Caring appears to be viewed at a very low level and to be taskfocused. Furthermore, caring around the birth process appears to be seen as best when it is hospital-based. Attention needs to be given to health information and health promotion. This concept was also studied through four focus groups held with women in the community. These data were analysed qualitatively. The findings revealed women’s dissatisfaction with the role and function of the nurse. Women’s lack of empowerment was evident in their encounters with health care professionals. Women related more negative than positive experiences of relationships with nurses. Perceptions of lack of trust and lack of concern, inter alia, in and from nurses were highlighted in the interviews. The concept “registered midwife” was studied by requesting registered midwives in a la. e academic hospital’s maternity unit to complete a questionnaire. The questionnaire aimed to obtam the midwives perceptions of the needs of women during pregnancy, labour and the puerperium. It also probed midwives perceptions of their roles and functions. The findings reveal that midwives recognise their teaching responsibility, but appear to have difficulty in meeting this responsibility. Her own education has prepared her for hospitalv based practice. Administration, research and policy-making are not priority roles for the majority of the respondents. “Curriculum” was studied through two questionnaires given to students in the B.Nursing programme. The findings revealed a need to increase curriculum content which relates to primary health care and a need to restructure practical learning opportunities as students do not feel compete,nt to practise in rural hospitals and community settings. The concept “outcome” was studied through two sets of focus groups. One with graduands who were currently in midwifery practice and the other with supervisors of these practitioners. The findings from the graduands’ groups highlighted the need for greater emphasis on culture, health information and promotion and holistic care in their learning experiences. The groups held with the nursing supervisors highlighted their perceptions of student needs and the inadequacy of the hospital as a learning environment. The findings from the four concepts have been used to develop a curriculum for Women’s Health. The curriculum model encapsulates Stufflebeam’s model and the concepts of the conceptual framework. The curriculum process utilizes problem-based learning and community-based education as the means to learning.
Keywords: Obstetrical Nursing; Education, Nursing